Pengaruh pH dan Konsentrasi Pada Penyerapan Ion Logam Cr(VI) Menggunakan Karbon Aktif Kulit Durian - Chairunnisa Chairunnisa; Edi Nasra (Jurnal Periodic Jurusan Kimia UNP, 2022)
Metal ions Cr (VI) are a type of toxic heavy metal that can cause environmental pollution. Chromium limits exceeding 0.1 mg/L in the water will cause damage to ecosystems and living things within them. Adsorption using activated carbon durian shell was chosen as one of the most efficient methods. Used adsorbent activated carbon durian shell that aims to know the quality of activated carbon durian shell and determine the optimum condition of absorption and optimum capacity of absorption of metal ions Cr (VI). The reaction between orange chromium ions with the addition of H2SO4 and colorless diphenylcarbazide forms a purple solution complex. Maximum wavelength absorption is obtained at 542 nm. The results were obtained with the capacity of immersion in optimum conditions to the absorption of metal ions Cr (VI) at pH 2 and Concentration 360 mg/L with an absorption capacity of 40,3190 mg/g. The study of adsorption isoterm refers more to the freundlich equation approach with a regression coefficient value approaching 1 (R2= 0,9684).